Ideological and thematic character of dastan "Zhusup – Zyliha" (Eurasian Journal of Philology Science and Education, 2015)
This article discusses issues related to the solution of complex problems, revealing the complex subject of humanity and the environment in the romantic epos Ali "Zhusup – Zyliha." Author reaches maximum aesthetic completeness through deeds Egyptian heroines, through the images of lovers in Zhusup through word – dedication to creating portrait Zhusup.Do not stay away from basic research and rich folk heritage of written records the Golden Horde . Comparing the typical motives Dastan genre, the main characters work, due to religious legends , the applicant identifies naturally close , traditional motifs of heroic tales and heroic epics Turkic Durbeka options . Completely mastered the great legacy of the poet Ali who introduced the Turkic world with ancient themes and motifs , originating from books such as the Torah and the Bible , the researcher chose the right path for the study of this complex subject in eastern literature. The author in the study clearly revealed in many different facets of samples Zhusup and change it. After that, he turned his attention to the special psychological elements of the great poetic version of Ferdowsi. He also found similarities Dastan options Jami "Zhusup – Zyliha" Nizami with the legend "Khosrow and Shyryn."
Keywords: variant; version; plot; psychology; detail; motif; image; Dastan; heritage; conflict; epic; tradition; episode.